Empowering women through better healthcare and nutrition in developing countries - International Conference on "Empowering Women in Developing Countries through Better Healthcare and Nutrition" (2010 : Birla Institute of Technology and Science); Sharma, Sheel, 1956-; Atero, Angella Atwaru, 1982-; Centre for Science and Technology of the Non-Aligned and Other Developing Countries (New Delhi : Centre for Science & Technology of the Non-Aligned and other Developing Countries : Regency Publications, 2012)
Papers presented at the International Conference on "Empowering Women in Developing Countries through Better Healthcare and Nutrition", held at Birla Institute of Technology and Science, Pilani, Rajasthan during 22-24 April 2010.
Includes bibliographical references.
Keywords: Women -- Health and hygiene -- Developing countries -- Congresses; Women -- Nutrition -- Developing countries -- Congresses; Medical policy -- Developing countries -- Congresses